Determinants of Export Competitiveness of Coffee Commodities in South Sulawesi - Ummul Khair; Sri Mardiyati; Amruddin; Mohammad Natsir; Muh. Arifin Fattah (Cita konsultindo, 2026)
Negotiation and strategic positioning in international trade are crucial for maximizing the economic benefits of agricultural commodities. This study aims to analyze the determinants of the export competitiveness of coffee from South Sulawesi, Indonesia, during the 2010–2024 period. The independent variables examined include coffee production capacity, world coffee prices, and the exchange rate of the Indonesian Rupiah (IDR) against the US Dollar (USD), while the dependent variable is export competitiveness, measured by the Revealed Comparative Advantage (RCA) index. Utilizing an Ordinary Least Squares (OLS) regression model, the findings reveal that the model explains 70.5% of the variance in coffee export competitiveness. Statistically, both coffee production and the exchange rate exhibit a significant negative impact on the RCA index, suggesting structural vulnerabilities related to supply quality and high dependency on imported agricultural inputs. Conversely, world coffee prices do not significantly influence export competitiveness, indicating the position of local exporters as price takers bound by long-term forward contracts. These findings emphasize the urgent need for strategic policy shifts from quantity-oriented agricultural expansion to quality standardization and upstream cost stabilization.